Body and embodiment in dance performance - Peng, Y. F.; Tanaka, A. (Proceedings of the 6th International Conference on Movement and Computing, 2019)
In this paper, we describe the definition of the body being extended by the concepts of other disciplines, such as philosophy, where some define it as decided by the potential of its actions. Inspired by these philosophical ideas of the body, a dance performance, Skin-awareness, was developed to explore and experiment with the body as a self-aware entity, embodying and interacting with artefacts and an immersive environment. The choreographic and technical design are introduced, followed by a composition of the work indicating where this research might lead.